ANALYSIS OF THE EFFECT OF CARE DOSE 4D SOFTWARE USE ON IMAGE QUALITY AND RADIATION DOSE ON THE CT SCAN ABDOMEN - Kartika Sari, Ni Larasati; Suzana, Merry; Muslim, Muzilman; Muliyati, Dewi (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
The CT Scan is the most significant contributor to radiation dose on radiological examination, although the frequency of the examination is far below other modalities. In order to control this radiation dose, manufactures of CT Scan have equipped their units with built-in software called Automatic Exposure Control (AEC). This study aims to analyze the effect of AEC software, CARE Dose 4D, on image quality, and CTDIvol. Objects used in this study were three water phantoms, each with a diameter of 165 mm, 230 mm, and 305 mm. The image quality-analyzed was CT Number and noise. Measurement of image quality was carried out following Bapeten's provisions. Noise Power Spectrum (NPS) graphics were also used to further observes noise texture. The CT Number accuracy, CT Number, and noise uniformity obtained with and without CARE Dose 4D, on the three phantoms were still within Bapeten's threshold. This indicates that the use of CARE Dose 4D can still image a homogeneous object accurately. The results of the NPS curve showed that the two modes, in three phantoms, were having the same noise texture. The NPS curves also showed that the use of CARE Dose 4D produces higher noise than the non-CARE Dose 4D mode. Meanwhile, there were significant differences from the CTDIvol obtained from the two modes. The use of CARE Dose 4D software reduced dose of up to 54.34%. From this, the use of CARE Dose 4D software can reduce the radiation dose while maintaining image quality.